THE LEGISLATION OF THE ROMANIAN PUBLIC ADMINISTRATION IN TODAY'S EUROPEAN CONTEXT - Florin STOICA (Challenges of the Knowledge Society)
In order to be able to adapt to the requirements of the current socio-economic and political context in which Romania is today, the public administration must strive for its efforts, perhaps more than ever, in the sense of its classic mission, namely the implementation of the law and providing quality public services. The connection to the European Central Public Administration obliges the public administration in Romania to keep up with the European trends in the field, and even contribute to the achievement of the Europe 2020 Strategy targets. Defective public administration legislation leads to a hindrance to a state's growth efforts. The modernization of the legislation, the modernization of the institutions in the field have the effects expected in the development of a state. If, since 1990, Romania has the excuse for the state in a "transition", a process that includes the state together with its institutions, the acceleration of the reform process can no longer be excusable due to the context. The integration of the Romanian state into the European space has come with a number of obligations but also rights, but in terms of obligations Romania is still outstanding. Political changes, frequent changes in parliamentary majority and ruling coalition have only increased the incapacity of the Romanian state to honor its obligations In line with European standards. But the common policy of the European community has not been blocked over time but has adapted to the challenges that international politics has provided, so Romania has to make major progress to assimilate the new challenges and honor its obligations.